Methodological Basis Of Teaching Uzbek Language In Secondary Schools (Example of Uzbek-language schools in Kazakhstan) (Journal of Pedagogical Inventions and Practices, 2022)
This article examines the organization of Uzbek language lessons in Uzbek schools in South Kazakhstan on the basis of innovative methods, the formation of students' speech in the classroom.